Juridical Implications of Postnuptial Agreement for Creditors from the Perspective of Legal Certainty - Galang Rasyiq Suyudi; Gusti Yosi Andri (Ann Publisher, 2026)
Background. The implementation of postnuptial agreements following the Constitutional Court Decision Number 69/PUU-XIII/2015 often creates legal uncertainty for creditors due to the sudden separation of assets carried out in the middle of a marriage. Aims. This study aims to analyze the juridical implications of making a marriage agreement after marriage on the position of the creditor as a third party from the perspective of legal certainty. Methods. The research method used is normative legal research with a statutory approach and a conceptual approach. Result. The results show that the separation of assets through a postnuptial agreement results in a change in the status of debt guarantees, which were originally community property into personal property, thereby potentially reducing the creditor's general security rights as regulated in Article 1131 of the Indonesian Civil Code. In order for such an agreement to be binding on third parties, the principle of publicity through registration with the relevant authorities (the Population and Civil Registry Office or the Office of Religious Affairs) must be strictly fulfilled. Without valid registration, the marriage agreement is only binding internally between the husband and wife and cannot be enforced against creditors. Conclusion. Legal protection for creditors can be pursued through preventive measures, such as asset status verification by a Notary before signing credit agreements, as well as repressive measures through the filing of an Actio Pauliana lawsuit if it is proven that the debtor acted in bad faith to evade collateral assets through the asset separation mechanism to avoid debt repayment.